Analisis Keterampilan Proses Sains Peserta Didik SMA Swasta dengan Akreditasi A Di Kecamatan Sukarami dan Kemuning Palembang - Anggraini, Della Tri; Hidayat, Saleh; Fadillah, Etty Nurmala (Universitas Negeri Makassar, 2018)
Abstract. The objective of this study is to determine the percentage of science process skills of private A accredited high school students in Kecamatan Sukarami and Kemuning. The researcher used descriptive-quantitative method.The sample were the tenth grade students of private high school with A acreditation in four school in Kecamatan Sukarami and Kemuning.The sample was chosen by using Purposive sampling. The data were obtained by using questionnaires, interviews, observations, multiple choice questions, and documentation. The results showed the percentage of the analysis of science process skills in Kecamatan Sukarami 63.22% (high) and Kemuning 61.25% (high). Kecamatan Sukarami obtained the percentage of indicators namely observing 71.72%, classifying 67.42%, interpreting 67.68%, forecasting 70.71%, formulating a hypothesis 57.07%, planning an experiment 55.05%, and communicating 44.44% . Kecamatan Kemuning obtained the percentage of indicators namely observing 69.22%, grouping 65.52%, interpreting 65.46%, forecasting 70.43%, formulating a hypothesis 50.47%, planning an experiment 51.55%, and communicating 47.85%. Keywords: science process skill, kecamatan sukarami and kemuning, high school students.